Issues of Ecological Education of Youth (The Peerian Journal, 2022)
Currently, due to the rapid development of scientific and technical development throughout the world, natural resources are increasingly involved in the economic cycle. In addition, the annual growth of the world's population requires the production of more food, fuel, clothing, etc. This causes the rapid reduction of the areas occupied by forests, the emergence of deserts, the destruction of soils, the depletion of the ozone layer located in the upper part of the atmosphere, the increase in the average temperature of the earth's air, and others.